Colossal magnetoresistance in Sr2-xNd1+xMn2O7 (x=0.0,0.1) - Battle, P; Blundell, S; Green, M; Hayes, W; Honold, M; Klehe, A; Laskey, N; Millburn, J; Murphy, L; Rosseinsky, M; Samarin, N; Singleton, J; et al. (1996)
Magnetization and magnetotransport measurements have been used to study the composition dependence of the electronic properties of the Ruddlesden-Popper phases Sr2NdMn2O7 and Sr1.9Nd1.1Mn2O7. Although their behaviour differs in detail, both compounds show a colossal magnetoresistance (CMR) effect (>10 000% in 14 T) in the temperature range 4.2 ≤ T/K ≤ 100. However, neither material shows a transition to a ferromagnetic state above 4.2 K, and both materials have higher resistivities (>103 Ω cm for 4.2 ≤ T/K ≤ 100) than the metallic oxides previously found to show CMR. In view of the low conductivity and the absence of ferromagnetism, the CMR of these phases is not readily explained by a doubleexchange mechanism.